Rozmieszczenie władzy w organizacji holdingowej - Haus, Ber (Division of power in a holding organization, 2005)
The author of this paper took the effort of explaining how is located the authority in the structure of holding. It has been concluded that despite of legal regulations the real corporate authority is focused in the areas of the bigger knowledge. The organic function and controlling move up the hierarchic structure of holding. The author hied to explain the reasons and results of such moving up of the corporate authority. Finally it has been concluded that in the global economy the role of the authority on the highest level of the corporation is permanently growing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 484-490